Impact of Moringa oleifera on the post-prandial blood glucose level among adults in Rawalpindi, Pakistan - Amer, Marryam; Fatima, Syeda Ammara; Gondal, Haji Hafiz Ubaid Ur Rehman; Iqbal, Amna; Warrarich, Bismah Imtiaz; Mehmood, Atif; Khan, Tayyab Mumtaz (International Journal Of Community Medicine And Public Health, 2023)
Background: Moringa oleifera (MO) has been used in the treatment of the Diabetes Mellitus (DM) all over the world. However, studies in Pakistan which show impact of MO on the blood glucose are lacking. This study was aimed to assess the impact of the MO leaf powder capsules on post-prandial blood glucose levels in diabetic and non-diabetic participants. Methods: This pilot study was conducted in a health care center, Rawalpindi, Pakistan among 14 diabetic and 14 non-diabetic participants for one year from January 2021 to December 2022. All participants were asked to fast for 12 hours on two occasions and each time their blood glucose levels were assessed via glucometer after giving bread. On first visit without MO capsules and on next visit with MO capsules. Data analysis was done by applying descriptive and paired t-test via SPSS version 25. Results: The mean values for study population of age, fasting blood glucose level, and post-prandial blood glucose level without giving MO capsules were, 51.50 with SD±5.28 year, 136.94 with SD±39.64 mg/dL, and 306.31 SD±151.35 mg/dL respectively. After 90 minutes of Intake of MO leaf powder capsule, the reduction in post-prandial blood glucose level in diabetic patients was significant (p=0.03), however, in non-diabetic healthy participants, it was statistically insignificant (p=0.08). No side-effects of MO were observed in any participant. Conclusions: In short, this study showed that Moringa oleifera ingestion decreases post-prandial blood glucose level significantly among diabetic, while not in non-diabetic. Moreover, intake of MO has no side effects.